Instrumental Role of Helicobacter pylori γ-Glutamyl Transpeptidase in VacA-Dependent Vacuolation in Gastric Epithelial Cells - Ling S.S.M. (Public Library of Science (PloS), 2018)
10.1371/journal.pone.0131460